The Moravian Countryside Illustrated with the Life of Pavel Petřík (1778-1829) - Petřík, Radek (Historica Olomucensia, 2021)
The present paper analyses life in Dub nad Moravou, a village in the countryside of the Haná region before the industrialisation period, illustrated with the life of the farmer Pavel Petřík (1778-1829). The case-based study maps the context of passing a farm on to the following generations. As the study has determined, for the period of one year after inheriting the farm, Pavel Petřík was obliged to provide his father with five measures or various crops for nourishment, and also had obligations towards his younger brother. The paper also describes the procedure of wedding feasts and related traditions and the form of corvée duties. On the farms of the Olomouc Chapter, the corvée took place six days a week in the period from the feast of St. John to the feast of St. Wenceslas. Pavel Petřík paid a regular yearly amount of 36 guldens and 31 kreuzers to the authorities. Among other things, he was obliged to annually bring three fathoms of wood for the authority from a distance of two miles and make three rides with unspecified cargo. He also paid 20 kreuzers to the Dubá parson. In addition, the study provides a demography-oriented view of the development of the family. The final part focuses on the last will being part of the farmer's bequest file. The study has contributed, particularly from the perspective of historical anthropology, to the knowledge of life in Moravian villages in the 1700s and 1800s. Literary sources from the Nenakonice archive, being almost completely preserved, may be used for further investigation into the history of the particular region.
Keywords: Dub nad Moravou; Microhistory; Farmer; Countryside; Servitude; Nenakonice; Manor; Archive sources